Aloe vera mucilage as an eco-friendly corrosion inhibitor for bronze in chloride media: Combining experimental and theoretical researches - Bouchra Benzidia; Mohammed Barbouchi; Malak Rehioui; Hind Hammouch; Hamid Erramli; Najat Hajjaji (Journal of King Saud University: Science, 2023)
Aloe vera (L.) Burm.F. (=Aloe barbadensis Mill.), a widely recognized medicinal plant, holds a prominent position due to its potent cosmetic and medicinal attributes. The objective of this work is to develop a new eco-friendly corrosion inhibitor for bronze B66 that is non-toxic, simple to apply, cost-effective, stable, and reversible. To achieve this goal, we initially devised an improved and cost-efficient method for extracting Aloe vera mucilage (AVM). Then we tested as corrosion inhibitor for bronze B66 in 3 % NaCl using gravimetric measurements, electrochemical methods and Scanning Electron Microscopy (SEM) coupled with Energy Dispersive X-Ray analysis (EDX). The electrochemical assessments validated the findings from the gravimetric analysis and demonstrated that our inhibitor significantly modifies the electrochemical process mechanism at the B66/3% NaCl interface. The corrosion rate of bronze decreases with the inhibitor's presence, and its inhibitory effectiveness amplifies with higher concentrations, reaching an efficiency of 86 % at 750 ppm. The mechanism of metallic copper and corrosion Acemannan inhibitor was explored through DFT studies and molecular dynamics simulation.